Pembinaan Santri Cilik (TK/TPA Desa Palae) Berbasis Praktik Ibadah dan Public Speaking sebagai Upaya Penguatan Nilai Keagamaan - Kusnadi Kusnadi; Imam Zarkasi Mubhar; Juliani; Rezki Aulia Pratiwi; Zulfira Luqmi; Indri Nurul Fitriani; Rezha Alfandi; Karmila Desiska; Zulfadli Achmad (LP2M Universitas Islam Ahmad Dahlan, 2026)
The development of young Islamic boarding school students (santri) at the Kindergarten/TPA (Teaching and Religious Education) in Palae Village is an important strategy for strengthening religious values ​​from an early age, integrated with the development of communication skills. This community service activity aims to: (1) improve understanding and skills in basic religious practices, including ablution, prayer, and memorization of short surahs; (2) develop public speaking skills as part of building students' self-confidence; and (3) shape adaptive and communicative religious character in social life. The implementation method uses a participatory approach through observation, program socialization, implementation of practice-based development, and evaluation through student performance assessments. The results of the activity show a significant increase in students' ability to carry out religious practices appropriately according to guidance and increased confidence in delivering religious material to a limited audience. The implications of this activity indicate that the integration of religious practice development and public speaking training is effective in strengthening the internalization of religious values ​​while developing students' communication competencies from an early age.